Student Preparation for Restricted Offline Learning (Case Study of Politeknik Indonusa Surakarta) - Cecilia Hadri; Sinta Novratilova; ADNAN AVIF (Indonesian Journal of Science and Education, 2022)
The explosion of COVID-19 cases in Indonesia starting in early July 2021 has gradually decreased significantly. Community participation to comply with government regulations is one of the keys to this success. The government has allowed learning to be conducted face-to-face on campus with various predetermined conditions. The success of this limited face-to-face learning program cannot spare students' readiness to follow all the rules, including the implementation of health protocols and vaccinations. This study aims to determine the understanding of students' attitudes and behavior towards COVID-19 during online learning. The study used a cross-sectional design with a sample of Indonesian Polytechnic students. The data was taken using an online questionnaire and then analyzed. Based on the data obtained, the level of student knowledge about COVID-19 is good. Students' attitude towards COVID-19 is also good, and most students are ready to vaccinate for health reasons. Students' behavior has also shown positive behavior, which means students are ready to carry out face-to-face learning in a limited manner with strict health protocols.